2016
DOI: 10.1177/0748730416642065
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Light Exposure in the Middle of the Night Disturbs the Circadian System and Emotional Regulation

Abstract: In mammals, the circadian system is composed of a principal circadian oscillator located in the suprachiasmatic nucleus (SCN) and a number of subordinate oscillators in extra-SCN brain regions and peripheral tissues/organs. However, how the time-keeping functions of this multiple oscillator circuit are affected by aberrant lighting environments remains largely unknown. In the present study, we investigated the effects of chronic light exposure in the middle of the night on the circadian system by comparing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 75 publications
1
13
1
Order By: Relevance
“…In contrast, mice exposed to long days consistently displayed 60–70% discrimination even though their behavior during training did not differ from control mice. This result is distinct from other models where cognitive deficits arise after exposure to non-naturalistic light manipulations (e.g., simulated jetlag, exposure to intermittent light pulses or above-threshold illumination throughout the night) 25, 41 . But our findings are consistent with previous work indicating that decreased intensity or length of daytime illumination produce affective and/or cognitive deficits in nocturnal and diurnal rodents 42, 43 .…”
Section: Discussioncontrasting
confidence: 88%
“…In contrast, mice exposed to long days consistently displayed 60–70% discrimination even though their behavior during training did not differ from control mice. This result is distinct from other models where cognitive deficits arise after exposure to non-naturalistic light manipulations (e.g., simulated jetlag, exposure to intermittent light pulses or above-threshold illumination throughout the night) 25, 41 . But our findings are consistent with previous work indicating that decreased intensity or length of daytime illumination produce affective and/or cognitive deficits in nocturnal and diurnal rodents 42, 43 .…”
Section: Discussioncontrasting
confidence: 88%
“…Of note, we also find that the timing of peak firing among VIP in cells is substantially more variable than that of VIP cells themselves, implying that these daily variations in firing do not entirely reflect a passive response to circadian rhythms in inhibitory GABAergic input from SCN VIP cells. Rhythmic expression of core clock genes has been observed in those locations where we find VIP in cells [53][54][55] , thus local clocks might also (directly or indirectly) contribute to the circadian variation observed in their activity. Similarly, SCN cells other than those that express VIP also send projections to SPZ, PVN and ventral thalamus [8][9][10] and could, in principle, also influence the firing of VIP in cells in some way.…”
Section: Discussionmentioning
confidence: 62%
“…Since chemogenetic inhibition of SCN VIP cells during their mid-day peak does not produce correspondingly large increases in heart rate, we infer that the ability of endogenous VIP cell firing to influence heart rate is restricted under our experimental conditions. This presumably reflects other ongoing rhythmic process that impact heart rate throughout the diurnal cycle, including gross changes in activity, arousal state and autonomic tone as well as potentially circadian clock mechanisms located in the heart and/or circuity downstream of the SCN [53][54][55]64 .…”
Section: Discussionmentioning
confidence: 99%
“…While both brain regions express the core clock components, there is some inconsistency regarding the timing of rhythmic clock gene expression in these areas. Many studies have found that in the BLA and sometimes in the CeA, Period ( Per1 , Per2 , and Per3 ) mRNA expression peaks in the night with PER2 protein expression lagging behind with a peak at the night–day transition (Chun et al., ; Harbour, Weigl, Robinson, & Amir, ; Ikeno & Yan, ; Lamont, Robinson, Stewart, & Amir, ; Moriya, Tahara, Sasaki, Ishigooka, & Shibata, ; Pantazopoulos, Dolatshad, & Davis, ). Rhythmic Bmal1 mRNA expression in the BLA or whole amygdala has been demonstrated in several studies but with variability in circadian phase (Chun et al., ; Moriya et al., ; Savalli, Diao, Schulz, Todtova, & Pollak, ).…”
Section: Telencephalon (Cerebrum): Amygdala and Bed Nucleus Of The Stmentioning
confidence: 99%